Analisis Kinerja Keuangan Berdasarkan Manajemen Persediaan dan Likuiditas pada PT Indofood CBP Sukses Makmur Tbk Periode 2019–2024 - Nidia Anggreni Das; Lili Wahyuni; Adel Ramadani Fitri; Iis Daryanti; Willa Demala Citra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Indofood CBP Sukses Makmur Tbk during the period of 2019–2024, with a focus on inventory management and liquidity aspects. Financial performance in this study is measured using the Return on Assets (ROA) ratio. Inefficient inventory management is identified as a trigger for rising storage costs, which ultimately has the potential to reduce the company's profitability level. The research method used is descriptive quantitative, with secondary data sources in the form of annual financial reports from the Indonesia Stock Exchange. The results show that inventory management fluctuated, with the highest turnover in 2019 (7.26 times) and the lowest in 2022 (6.03 times), which linearly affected the decline in ROA to 3.98% in the same year. Meanwhile, the liquidity aspect projected through the current ratio showed a significant strengthening trend, reaching 4.09 times in 2024. This indicates the company's highly conservative post-pandemic resilience strategy, which however risks creating a phenomenon of idle assets. The study concludes that although financial security is maintained, optimizing operational turnover remains the key to boosting the company's profitability again.